Vehicle-2-Vehicle Communication Based on Wireless Sensor Network - S. Sinthuja; S. V. Saravanan (Bulletin of Electrical Engineering and Informatics, 2017)
Truck Platooning is a car innovation that permits gathering various trucks into a single element where one truck intently takes after the other that outcomes in an expanded street limit. This kind of detachment allows to a significant degree tight separations and synchronous driving between the vehicles.  Our point is to plan and exhibit a self-ruling truck platooning framework given vehicle-to-vehicle (V2V) correspondence innovation. The structure utilises IEEE 802.15.4 remote convention joined with separation going sensors to enable vehicles inside the company to safely trade data progressively and naturally break and quicken in light of the lead truck. The rapid of remote correspondence permits to a significant degree tight separations and synchronous driving between the platooning vehicles.